Prediction of failure of sands under constant volume general cyclic simple shear loading using specific dissipated energy - Zavala Rosell, Guillermo José (Pontificia Universidad Católica del Perú, 2023)
Seismic soil liquefaction is a recurring phenomenon that may cause significant damage to infrastructure during earthquakes and that in turn may also cause injuries and even fatalities. This phenomenon has been widely studied by researchers, and for its study the laboratory characterization of behavior of sands when subjected to cyclic loading is very important. One of the approaches for this kind of studies is through the calculation of the energy that is dissipated by the soil when it is subjected to cyclic loading. One of the hypotheses for utilizing these energy methods states that the cumulative dissipated energy required in a soil to reach failure only depends on the initial state of the sample (relative density and initial vertical effective stress) and should be reasonably constant and independent of the loading amplitude and waveform applied to the sample. This thesis work seeks to evaluate the validity of this hypothesis. Also, based on this hypothesis, it seeks to develop a simplified methodology to predict failure of sands when subjected to general cyclic loading, performing only simple harmonic tests. The hypothesis for the development of this methodology is that there is a relationship between the initial state of the sample and the cumulative dissipated energy to failure in cyclic simple shear test. To reach these goals, over 250 uniform and non-uniform constant volume cyclic simple shear tests were performed on Ottawa 20/30 sand, and the dissipated energy to failure was measured in each of these tests. The experimental program showed that the measured cumulative dissipated energy to failure was reasonably constant for the same initial sample conditions, but with some variability inherent to geotechnical laboratory testing. As expected, the cumulative dissipated energy increased with increasing initial stress level and relative density. Also, a simplified method to predict the dissipated energy to failure of a sample subjected to general cyclic loading, based on a multivariable regression performed on a simplified set of laboratory results, is presented, and it is next validated with two independent data sets. In both cases the method was found to yield reasonable predictions of failure of sands when subjected to complex and irregular cyclic shear loading.

La licuefacción sísmica del suelo es un fenómeno recurrente que puede causar daños significativos a la infraestructura durante los terremotos, y que también puede causar lesiones e incluso muertes. Este fenómeno ha sido ampliamente estudiado por los investigadores, y para su estudio es muy importante la caracterización del comportamiento de las arenas en el laboratorio, cuando se someten a esfuerzos cíclicos. Este tipo de estudios se pueden realizar calculando la energía disipada por el suelo cuando éste es sometido a cargas cíclicas. Una de las hipótesis para utilizar estos métodos de energía establece que la energía disipada acumulada requerida para alcanzar la falla en un suelo solo depende del estado inicial de la muestra (densidad relativa y esfuerzo efectivo vertical inicial) y que debe ser razonablemente constante e independiente de la carga, amplitud y forma de onda aplicada a la muestra. Este trabajo de tesis busca evaluar la validez de esta hipótesis. Asimismo, con base en esta hipótesis, se busca desarrollar una metodología simplificada para predecir la falla de arenas cuando se someten a cargas cíclicas generales, realizando únicamente ensayos armónicos simples. La hipótesis para el desarrollo de esta metodología es que existe una relación entre el estado inicial de la muestra y la energía disipada acumulada hasta la falla en el ensayo cíclico de corte simple. Para alcanzar estos objetivos, se realizaron más de 250 ensayos de corte simple cíclico a volumen constante, uniformes y no uniformes, en arena Ottawa 20/30, y se midió la energía disipada hasta la falla en cada uno de estos ensayos. El programa experimental mostró que la energía disipada acumulada medida hasta la falla fue razonablemente constante para las mismas condiciones iniciales de la muestra, pero con cierta variabilidad inherente a las pruebas geotécnicas de laboratorio. Como se esperaba, la energía disipada acumulada aumentó con el aumento del nivel de esfuerzo inicial y la densidad relativa. Además, se presenta un método simplificado para predecir la energía disipada hasta la falla de una muestra sujeta a carga cíclica general, basado en una regresión multivariable realizada en un juego simplificado de resultados de laboratorio, y luego se valida con dos juegos de datos independientes. En ambos casos, se encontró que el método proporcionaba predicciones razonables de falla de arenas cuando se sometían a cargas cíclicas de corte irregulares y complejas.
Keywords: Suelos--Efectos sísmicos; Mecánica de suelos--Ensayos; Suelos--Licuefacción--Metodología; https://purl.org/pe-repo/ocde/ford#2.00.00